Synthesis of 3-Substituted 2-Aminopyridines via Displacement of 3-Fluoro-2-nitropyridine - Culshaw, Janet D.; Eden, Jonathan M.; Ford, Susannah J.; Hayter, Barry; Perkins, David R.; Pike, Kurt G. (Synlett, 2012)
An efficient method for the substitution of 3-fluoro-2-nitropyridine with a range of nitrogen-containing heterocycles and aliphatic amines is described. The reaction proceeds in a regioselective manner at moderate temperature and in reasonable yield.
Keywords: nitrogen-containing heterocycles; 3-fluoro-2-nitropyridine; 3-substituted 2-aminopyridines; aliphatic amines